Architecting Enterprise Managing Innovation, Technology, and Global Competitiveness - Rajagopal, . (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
The discussion in this book provides an introduction to the concept of entrepreneurship and entrepreneurial business management. The author covers many elements of the entrepreneurial management discipline including choosing a business, organizing, financing, marketing, developing an offering that the market will value, and growing a business.